Taxonomic notes on the spider genus Messapus Simon, 1898 (Araneae, Corinnidae), with the description of the new genera Copuetta and Wasaka and the first cladistic analysis of Afrotropical Castianeirinae - Haddad, Charles R. (Zootaxa, 2013)
The Afrotropical sac spider genus Messapus Simon, 1898, presently placed in the Castianeirinae, is reviewed. The type material of the type species, M. martini Simon, 1898, clearly represents two different species, a corinnine female (here designated the lectotype) and a castianeirine male (the paralectotype). The female is redescribed and its corresponding male is described for the first time. As a result, Messapus is transferred to the Corinninae. Corinna natalis Pocock, 1898 is transferred to Messapus, while Messapus secundus Strand, 1907 is transferred to Merenius Simon, 1909. The new genus Copuetta gen. nov., with the type species C. maputa sp. nov., is established to accommodate the misidentified castianeirine male paralectotype of M. martini, and its matching female is described for the first time. Castianeira kibonotensis Lessert, 1921 syn. nov. is considered a junior synonym of Copuetta lacustris (Strand, 1916) comb. nov., which is redescribed from both sexes and transferred from Copa Simon, 1885. A further eleven new species of Copuetta are described: C. comorica sp. nov., C. erecta sp. nov., C. kakamega sp. nov., C. kwamgumi sp. nov., C. lesnei sp. nov., C. litipo sp. nov., C. lotzi sp. nov., C. magna sp. nov., C. naja sp. nov., C. uzungwa sp. nov. and C. wagneri sp. nov. Of these species, only C. lacustris and C. magna sp. nov. have large distribution ranges. Seven of the species are only known from the type locality and the remaining four have distributions restricted to one or two countries. A second new genus, Wasaka gen. nov., is described for four new species with restricted distributions from East and Central Africa: W. imitatrix sp. nov., W. montana sp. nov., W. occulta sp. nov. (type species) and W. ventralis sp. nov. A first phylogenetic analysis focused on the Afrotropical Castianeirinae is presented. The results support the placement and transfer of Messapus (including M. natalis comb. nov.) and Medmassa Simon, 1887 in the Corinninae, and the monophyly of a clade including the four cryptic lycosiform castianeirine genera from the Afrotropical Region (Copa, Copuetta gen. nov., Echinax Deeleman-Reinhold, 2001 and Wasaka gen. nov.). The implications of the phylogenetic results are briefly discussed.